A novel difficulty scoring system of laparoscopic liver resection for liver tumor - Xi, Cheng; Zhu, Maoqun; Ji, Tianhao; Tan, Yulin; Zhuang, Lin; Yuan, Zhiping; Zhang, Zheng; Xu, Litian; Liu, Zhilin; Xu, Xuezhong; Xue, Wenbo; Ding, Wei (Frontiers in Oncology, 2022)
Objectives: To develop a novel difficulty scoring system (NDSS) to predict the surgical difficulty of laparoscopic hepatectomy. Patients and Methods: A total of 138 patients with liver tumors performed liver resection (LLR) between March 2017 to June 2022 were selected from Affiliated Hospital of Jiangnan University and Wujin Hospital Affiliated with Jiangsu University. Patient demographics, laboratory tests, intraoperative variables, pathological characteristics were assessed. We also assessed the Child Pugh score and the DSS-B score. Results: Patients were divided into training and testing cohort according to their hospital. Patients in training cohort were divided into high and low difficult groups based on operation time, blood loss and conversion. Higher percentage of patients with malignant liver tumor (87.0% vs. 58.1%; P = 0.003) or history of hepatobiliary surgery (24.1% vs. 7.0%; P = 0.043) in high difficult group than in low difficult group. To improve the difficulty scoring system, we incorporated the history of hepatobiliary surgery and nature of the tumor. A novel difficulty scoring system was established. The results showed that the operation time (P < 0.001), blood loss (P < 0.001), ALT (P < 0.001) and AST (P = 0.001) were associated with the novel difficulty score significantly. Compared with DSS-B, the NDSS has a higher area under the receiver operating characteristic (AUROC) (0.838 vs. 0.814). The nomogram was established according to the NDSS. The AUROCs of the nomogram in training and testing cohort were 0.833 and 0.767. The calibration curves for the probability of adverse event showed optimal agreement between the probability as predicted by the nomogram and the actual probability. Conclusions: We developed a nomogram with the NDSS that can predict the difficulty of LLR. This system could more accurately reflect the difficulty of surgery and help liver surgeons to make the surgical plan and ensure the safety of the operation.